2017
DOI: 10.1186/s40645-017-0126-9
|View full text |Cite
|
Sign up to set email alerts
|

Seismic imaging of slab metamorphism and genesis of intermediate-depth intraslab earthquakes

Abstract: We review studies of intermediate-depth seismicity and seismic imaging of the interior of subducting slabs in relation to slab metamorphism and their implications for the genesis of intermediate-depth earthquakes. Intermediate-depth events form a double seismic zone in the depth range of c. 40-180 km, which occur only at locations where hydrous minerals are present, and are particularly concentrated along dehydration reaction boundaries. Recent studies have revealed detailed spatial distributions of these even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 152 publications
1
31
0
Order By: Relevance
“…We note that Wells et al (2017) have highlighted a statistically significant, alongstrike anticorrelation between tremor density and the presence of major crustal faults, suggesting that these deep faults are able to disrupt the plate boundary seal and, locally, tap fluids from the LVZ, thereby reducing tremor density. Hasegawa and Nakajima (2017) have also suggested that the spatial anticorrelation of LFEs and high levels of crustal seismicity observed at the Kii and Ise Gaps in southwest Japan, can be explained by a permeable fore arc that drains fluids at the megathrust, with these fluids migrating through crustal faults, reducing their shear strength, and promoting metamorphic reactions. The deep clusters of microseismicity below this structure in the vicinity of Victoria, displayed in Figure 6, may therefore manifest localized fluid delivery from the slab.…”
Section: Discussionmentioning
confidence: 99%
“…We note that Wells et al (2017) have highlighted a statistically significant, alongstrike anticorrelation between tremor density and the presence of major crustal faults, suggesting that these deep faults are able to disrupt the plate boundary seal and, locally, tap fluids from the LVZ, thereby reducing tremor density. Hasegawa and Nakajima (2017) have also suggested that the spatial anticorrelation of LFEs and high levels of crustal seismicity observed at the Kii and Ise Gaps in southwest Japan, can be explained by a permeable fore arc that drains fluids at the megathrust, with these fluids migrating through crustal faults, reducing their shear strength, and promoting metamorphic reactions. The deep clusters of microseismicity below this structure in the vicinity of Victoria, displayed in Figure 6, may therefore manifest localized fluid delivery from the slab.…”
Section: Discussionmentioning
confidence: 99%
“…Green arrows indicate the location of the upper‐plane seismic belt in the crust discussed in the text. Gray dashed lines denote the inferred location of the Kyushu‐Palau Ridge (KPR) taken from Hasegawa and Nakajima (). The location of Cluster A1 is indicated by black arrows in (a).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Hasegawa and Nakajima () pointed out that the upper‐plane seismic belt, which is defined as a belt‐like concentration of crustal seismicity distributed subparallel to the slab isodepth contours (Kita et al, ), is observed at depths of 50–70 km beneath central and southern Kyushu. Our classification of earthquakes shows that concentrated crustal seismicity is observed along the slab isodepth contour of ~60 km (green arrows in Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…Although dehydration appears to be an important factor in a wide range of slabs, the mechanism by which it actually enables earthquakes could differ depending on the location of seismicity and several hybrid mechanisms involving dehydration have been proposed in the literature. Embrittlement from blueschist‐facies dehydration may be more important in the upper plane of cold slabs like the Pacific (Okazaki & Hirth, ) whereas elsewhere, thermal shear instabilities can also be triggered by initial dehydration (Hasegawa & Nakajima, ). Ferrand et al () suggested from lab‐based evidence that dehydration reactions can enable intermediate‐depth earthquakes through stress transfer from dehydrating antigorite clusters to a surrounding olivine matrix rather than fluid overpressure, which also allows for strain localization followed by acceleration of said localization, a process termed “dehydration‐driven stress transfer” (DDST).…”
Section: Discussionmentioning
confidence: 99%